TUBERCULOSIS AS THE RESULT OF THE IMMUNE RECONSTITUTION INFLAMMATORY SYNDROME AFTER INITIATION OF ANTIRETROVIRAL THERAPY - Корж, Е. В.; Гуренко, Е. Г. (University Clinic; No 4(29) (2018): UNIVERSITY CLINICDO - 10.26435/uc.v0i4(29).225, 2018)
Initiation of antiretroviral therapy in HIV-infected individuals carries a high risk of immune reconstitution inflammatory syndrome with manifestation of previously not diagnosed infections, including tuberculosis. The aim of the study was to estimate the clinical and radiological features and effectiveness of treatment of tuberculosis that developed as a result of immune reconstitution inflammatory syndrome after the initiation ART in HIV-infected patients. Material and methods. 24 medical records of inpatients with co-infection tuberculosis/HIV who were treated in the Donetsk Republican Clinical Tuberculosis Hospital were analyzed. All patients developed tuberculosis within the first three months after initiation of antiretroviral therapy. At the pre-hospital stage, all patients before starting antiviral treatment were examined (objective examination, chest X-ray, content of CD4 in the blood). Results and discussion. Before initiation of antiretroviral therapy, the medians of CD4 content were 35 cells/μL and 4.7%, 7 persons (29.2%) had no complaints, 13 (54.2%) complained of fiver, 12 (50.0%) of weakness, 8 (33.3%) of cough with a sputum, 4 (16.7%) of weight loss, and 2 persons (8.3%) had neurological symptoms. X-ray normal picture of the chest was determined in 11 persons (45,8%), 13 persons (54.2%) had an intensification of the pulmonary marking, 6 (25,0%) – increased intrathoracic lymph nodes. The first symptoms of tuberculosis appeared within 3 to 60 days, the median was 19 days, all patients noted fiver, 9 persons (37.5%) had signs of tuberculous meningitis, 17 (70.8%) had generalized tuberculosis. During a stationary period of treatment, 14 people died (58.3%). From 9 patients with tuberculous meningitis, seven persons (77.8%) died. 8 people (33.3%) successfully completed a stationary anti-tuberculosis chemotherapy and were discharged to continue treatment at home. Conclusions. Tuberculosis, which develops as a result of the immune reconstitution inflammatory syndrome, occurs in HIV-infected individuals with severe immunodeficiency when prescribing antiretroviral therapy without anti-tuberculosis drugs, characterized by generalized forms in 70.8% and high hospital mortality, reaching 58, 3%. Especially malignant course has tuberculous meningitis, lethality reaches 77.8%. Before starting antiviral treatment in 54.2% of patients fever and intensification of the pulmonary marking was noted, in 25.0% – an increased intrathoracic lymph nodes. The presence of complaints and X-ray changes is the basis for delaying antiretroviral therapy and additional examination of patients. If it is impossible to verify the cause of these disorders, it is advisable to start antiviral therapy under the cover of anti-tuberculosis chemotherapy, however, its schemes and duration need clear regulation.